Membrane Sweep and Stretch at Term Pregnancy: Preventing Prolonged Pregnancy - Shams, Roeda; Nasreen, Abida (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Artificial initiation of labour process before its spontaneous onset is common procedure conducted in all essential obstetric units. Prolong pregnancy is considered to be most common indication for induction of labour. Waiting for spontaneous labour after 41 weeks of gestation and formal induction of labour both carries maternal and fetal risk. The average induction rate of our OBGYN unit is 23%compare to 13-20% of UK and United states. The main purpose of study was to observe whether a non-pharmacological method of induction, membrane sweeping can prevent prolong pregnancy and reduce need for formal induction. RESULTS: This study was conducted on 100 patients. 56 patients were multiparous and 44 patients were primiparous. 63 patients presented with active labour with in next 14 days. 11 patients presented with PROM, 21(21%) went beyond 40 weeks and were formally induced (2% reduction). The initial bishop scoring was <8(poor) in 56 patients and >8 (favorable)in 44 patients. Bishop scoring was an important element in increasing chance of initiation of labour. (48%) patients who presented with active labour were in poor bishop group while 36(81%) from favorable bishop score. CONCLUSION: Routine sweep and stretch or membrane sweeping at 38 weeks does not reduces prolong pregnancy and hence need for formal induction. KEY WORDS: Sweep and stretch, prolong pregnancy, induction